Practical guide to environmental economics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Values for the environment, a guide to economic appraisal by T Winpenny 1991 277pp UKL 14.95 ISBN 0 11 580257 6 HMSO, PO Box 276 London SW8 5DT, UK